GEOCHEMISTRY STUDY AND MATURITY MODELING BASED ON VITRINITE REFLECTANCE ON TALANGAKAR FORMATION, IN SAKAKEMANG AREA, JAMBI SUB BASIN, SOUTH SUMATRA BASIN - DODI WIRASATIA (NIM: 22011303); Pembimbing : Prof. Dr. Ir. Eddy Ariyono Subroto; Dr. Ir. Asep Her,
The purpose of this study is to indetify source rock potential in Talangakar Formation based on organic richness, kerogen type, maturity, and understanding geology conditions to produce hydrocarbon which includes subsurface, burial histroty, and maturity modeling. Source rock evaluation uses TOC data, S1, S2, tmax, vitrinite reflectance, and oil biomarkers to determine depositional environments and oil to oil correlation. Maturity modeling using the existing data on the burial history such as vitrinite reflectance, BHT, porosity, and biostratigraphy. The sesults of seismic data indicates there are three graben which East Ketaling graben, Merang, and Tamiang. In general, sediment configuration will be increasingly shallow to the east and south, and will be deeper to the west and the north area of research. The results of source rock analysis showed that kerogen types in the study area is type III kerogen which tend to produce gas. The result of correlation between oil to oil consists of two families that is Family A and Family B. Family A (Lubuk Batu-14 and Kukulambar-1) is transitional depositional environment with marine influence which organic material derived from marine algae and there are some organic material from terrestrial. Family B (Pandai-1) is the transitionanl depositional environment with terrestrial influence which organic material derived from higher plants. Source rock maturity map in Talangakar Formation at present day shows that maturity (based on Ro) source rock in Sungai Medak-1 is 0.79%, Kukulambar-1: 0.81%, and Dabuk-1: 0.71%, already reached into peak mature, while Kubu-1 and the surrounding area has immature stage because high area and did not quite enough to burial. Migration map show oil at Kukulambar-1 and Pandai-1 are derived from Merang graben and oil at Lubuk Batu-14 is derived from Tamiang graben. It was predicted that oil at Kukulambar-1 and Lubuk Batu-14 in Baturaja Formation comes from Talangakar Formation with marine environment, meanwhile oil at Pandai-1 that situated n Talangakar Formastion was presumed to be ferom from Talangakar Formation with terrestrial environment.